2023
DOI: 10.1097/cxa.0000000000000173
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Inpatient Addiction Consult Services: A Systematic Review and Narrative Synthesis

Abstract: Background: Addiction Consult Services (ACS) have become an emergent clinical intervention for persons with substance use disorders (SUD) requiring hospital-based care. However, there have been few recent evaluations of the evidence for the effectiveness of ACS on SUD outcomes.Objective: We aimed to assess the effectiveness of ACS for persons with SUD on a range of SUD-related outcomes.Methods: We systematically reviewed peer-reviewed scientific literature measuring ACS outcomes. We searched 5 electronic sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…38 Alternatively, implementation of a hospital ACS may reduce provider stigma through exposure to a harm-reduction philosophy and ability to offer effective SUD treatment. 33,39,40…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38 Alternatively, implementation of a hospital ACS may reduce provider stigma through exposure to a harm-reduction philosophy and ability to offer effective SUD treatment. 33,39,40…”
Section: Discussionmentioning
confidence: 99%
“…38 Alternatively, implementation of a hospital ACS may reduce provider stigma through exposure to a harmreduction philosophy and ability to offer effective SUD treatment. 33,39,40 Previous research has identified both stigma and a lack of provider knowledge of clinical guidelines as reasons patients experience opioid withdrawal in healthcare settings. 23,28 Our study advances these findings by highlighting the difficulty some hospital providers had differentiating specific withdrawal symptoms, which could delay appropriate opioid withdrawal treatment.…”
Section: Discussionmentioning
confidence: 99%